Increasing hospital admission rates and economic burden for colorectal cancer in Brazil, 1996-2008 Aumento de las tasas de ingresos hospitalarios por cáncer colorrectal y su carga económica en Brasil, 1996-2008 - Ulysses dos Santos Torres; Thomas Eugenio Portes de Almeida; João Gomes Netinho (Pan American Health Organization, 2010)
OBJECTIVE: To determine the trends in hospital admission rates for colorectal cancer (CRC) in the Brazilian Public Health System from 1996 to 2008 and to assess the economic costs. METHODS: Data from the Hospital Information Systems database of the Brazilian Unified Health System were used for analysis of all admissions with a primary diagnosis of CRC between 1996 and 2008. RESULTS: There were 297 108 CRC admissions over the study period, with an annual increase from 12 821 in 1996 to 35 040 in 2008. Age-standardized admission rates increased from 8.7 to 23.56 per 100 000 for a percentage increase of 171%. The average length of stay decreased from 11.6 days in 1996 to 7.5 days in 2008. The average hospital mortality declined from 10.4% to 8.5%. Overall costs in United States dollars (US$) of CRC hospitalizations rose from US$ 16.5 million in 1996 to US$ 33.5 million in 2008; the average cost of each admission, however, decreased from US$ 1 283 to US$ 954. CONCLUSIONS: Hospitalization rates for CRC in Brazil significantly increased during a 13-year period, incurring a considerable rise in the inflation-adjusted economic burden; national in-hospital mortality rates have remained relatively high. OBJETIVO: Determinar las tendencias de las tasas de ingresos hospitalarios por cáncer colorrectal (CCR) en el sistema de salud pública brasileño de 1996 al 2008 y evaluar sus costos económicos. MÉTODOS: Se utilizó la información de la base de datos de los sistemas de información de los hospitales del Sistema Único de Salud brasileño con objeto de analizar todos los ingresos con diagnóstico primario de CCR entre 1996 y el 2008. RESULTADOS: Durante el período de estudio, se produjeron 297 108 ingresos por CCR, con un aumento anual de 12 821 en 1996 a 35 040 en el 2008. Las tasas de ingresos estandarizadas según la edad aumentaron de 8,7 a 23,56 por 100 000, con un aumento porcentual de 171%. La estancia hospitalaria media disminuyó de 11,6 días en 1996 a 7,5 días en el 2008. La mortalidad hospitalaria promedio descendió de ...